The Impact of Insecticides on Mycelial Growth of Metarhizium spp. and Their Efficacy in Controlling Larvae and Pupae of the House Fly (Musca domestica L.) - Duanpen Wongsorn; Benya Saenmahayak; Nittaya Pitiwittayakul; Surachai Rattanasuk (Tropical Life Sciences Research, 2025)
Metarhizium spp. are entomopathogenic hyphomycete fungi with great potential as biological control agents against insects and as a component within integrated pest management systems. This study evaluated 10 Metarhizium spp. isolates for their effectiveness against house fly larvae and pupae. The isolates with the highest infection rates were tested for compatibility with insecticides. NMMet_SS9/2 and NMMet_CLPK4/1 were the most effective, with infection rates of 86.67% and 60.00% for larvae and pupae, respectively. Both isolates were cultured on Potato Dextrose Agar (PDA) mixed with Cypas® 250 EC (100 mL and 50 mL per 6.25 L) and Tanidil®-T (100 g/L and 50 g/L) to assess the impact of insecticides on mycelial growth. After 28 days, the radial growth of NMMet_SS9/2 (81.33 mm) and NMMet_CLPK4/1 (77.67 mm) on PDA with Cypas® 250 EC (50 mL per 6.25 L) showed no significant differences (p > 0.05) compared to growth on PDA alone. Aspore suspension (1 × 10? spores/mL) of NMMet_SS9/2 and NMMet_CLPK4/1 cultured on PDA with Cypas® 250 EC (50 mL per 6.25 L) was used to control house fly larvae and pupae, resulting in mortality rates of 93.33% (NMMet_SS9/2) and 75.56% (NMMet_CLPK4/1), with infection rates of 77.78% and 71.11%, respectively. No significant differences (p > 0.05) were observed in mortality or infection rates compared to spores cultured on PDA without insecticides. These findings confirm that NMMet_SS9/2 and NMMet_CLPK4/1 are highly effective against house fly larvae and pupae and can proliferate on media containing Cypas® 250 EC at 50 mL per 6.25 L without compromising their insecticidal properties, making them promising candidates for integrated pest management strategies.